A simple electrochemical immunosensor based on a chitosan/reduced graphene oxide nanocomposite for sensitive detection of biomarkers of malignant melanoma. Issue 40 (12th September 2022) - Zhang, Huihua; Qu, Hui; Cui, Jingbo; Duan, Linxia
Abstract : Simple electrochemical immunosensor is easily fabricated based on chitosan/reduce graphene oxide nanocomposite for sensitive determination of a tumor marker of malignant melanoma. Abstract : The sensitive and specific detection of tumor biomarkers is crucial for early diagnosis and treatment of malignant melanoma. Immunoassay with a simple sensing interface and high sensitivity is highly desirable. In this work, a simple electrochemical immunosensor based on a chitosan/reduced graphene oxide (CS–rGO) nanocomposite was developed for sensitive determination of an S-100B protein, a tumor marker of malignant melanoma. CS–rGO nanocomposite were prepared by chemical reduction of graphene oxide in the presence of chitosan and modified on glassy carbon electrode (GCE) to provide a biofriendly, conductive, and easily chemically modified matrix for further immobilization of antibodies. Anti-S-100B antibodies were grafted onto the chitosan molecules to fabricate the immunorecognition interface by a simple glutaraldehyde cross-linking method. Electrochemical determination of S-100B was achieved by measuring the decreased current signal of solution phase electrochemical probes, which originated from the increased steric hindrance and insulation caused by the formation of antigen–antibody complexes at the electrode interface. Due to the good conductivity, high surface area, excellent biocompatibility, and good film-forming ability of CS–rGO, the constructed immunosensor exhibited good stability, high selectivity and sensitivity, a wide dynamic range from 10 fg mL −1 to 1 ng mL −1 and a low limit of detection of 1.9 pg mL −1 (S/N = 3). Moreover, the sensor was also applicable for the sensitive detection of S-100B protein in real human serum samples.